Struktur Modal: Ditinjau dari Karakteristik Perusahaan yang Terdaftar di Jakarta Islamic Index 70 (JII70) - Cahya, Bayu Tri; Nafiah, Siti; Suparwi, Suparwi; Kurniawan, Danang (BISNIS, 2019)
Capital structure is a combination of long-term debt and the company's own capital in the form of retained earnings and the issuance of shares. This study aims to determine the effect of size, asset structure, and profitability on the capital structure of companies registered in the Jakarta Islamic Index 70. Jakarta Islamic Index 70 (JII70) is a sharia stocks index that was just launched in 2018. This research design is quantitative. The population in this study is companies listed on the Jakarta Islamic Index 70 during the 2018 period. The sample in this study was 51 company stocks. The techniques in this study are classic assumptions and multiple linear regression analysis. The results of this study indicate that the Asset Structure affects the capital structure. While profitability and size do not affect capital structure.